Validity of Anti-PSMA ScFvD2B as a Theranostic Tool: A Narrative-Focused Review - Barbara Frigerio; Elena Luison; Alessandro Desideri; Federico Iacovelli; Chiara Camisaschi; Ettore C. Seregni; Silvana Canevari; Mariangela Figini (Biomedicines, 2021)
Prostate cancer (PCa) is the second leading cause of cancer among men, and its diagnosis and adequate staging are fundamental. Among the biomarkers identified in recent years for PCa management, prostate-specific-membrane-antigen (PSMA), physiologically expressed at a low level on healthy prostate and in other normal tissues and highly overexpressed in PCa, represents a reliable marker ideal for imaging and therapy. The development of anti-PSMA antibodies, such as D2B, demonstrated slow clearance of intact antibodies compared with fragments resulting in low tumor-to-blood ratios; however, the modular structural and functional nature of antibodies allowed the generation of smaller fragments, such as scFvs. In this review of the anti-PSMA antibody fragment scFvD2B, we combined further characterization of its biomolecular and tissue cross-reactivity characteristics with a comprehensive summary of what has already been performed in preclinical models to evaluate imaging and therapeutic activities. A molecular dynamics study was performed, and ScFvD2B occupied a limited conformational space, characterized by low-energy conformational basins, confirming the high stability of the protein structure. In the cross-reactivity study, the weak/absent immunoreactivity in non-tumor tissues was comparable to the PSMA expression reported in the literature. Biodistribution studies and therapeutic treatments were conducted in different animal models obtained by subcutaneous or locoregional injection of PSMA-positive-versus-negative xenografts. The maximum tumor uptake was observed for 123I(SPECT), 124I(PET), and optical imaging, which avoids kidney accumulation (compared with radiometals) and leads to an optimal tumor-to-kidney and tumor-to-background ratios. Regarding its possible use in therapy, experimental data suggested a strong and specific antitumor activity, in vitro and in vivo, obtained using CAR-T or NK-92/CAR cells expressing scFvD2B. Based on presented/reviewed data, we consider that scFvD2B, due to its versatility and robustness, seems to: (i) overcome some problems observed in other studied scFvs, very often relatively unstable and prone to form aggregates; (ii) have sufficient tumor-to-background ratios for targeting and imaging PSMA-expressing cancer; (iii) significantly redirect immune killing cells to PSMA-positive tumors when inserted in second-generation CAR-T or NK-92/CAR cells. These data suggest that our product can be considered the right reagent to fill the gap that still exists in PCa diagnosis and treatment.